Philosophical background of literary category "event" (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article is devoted to defining the role of philosophy in a highly complex process of development of the literary category «event». The text illustrated the essence, the types, the features, the functions of the category «event» that based on analysis of the works of the philosophers different time. The author states that the philosophical basis became impetus for future of research and specification of the literary category «event».
Keywords: event; the literature category «event»; the event in literature; the event in philosophy